The Financial Performance Reviewed Through Liquidity and Market Ratio - Ameliana, Hesty; Octafian, Ray (Journal of International Multidisciplinary Research, 2024)
This research aims to investigate the financial performance of a company by focusing on liquidity ratio analysis and market ratio analysis. Financial performance is a key indicator in evaluating the stability and financial efficiency of a company. Liquidity ratios and market ratios are used to measure the financial performance of PT Gudang Garam Tbk as a case study during the period 2021-2023. By analyzing liquidity ratios and market ratios, this research aims to provide a deeper understanding of the financial health and market valuation of PT Gudang Garam Tbk. The research findings explain that overall, PT Gudang Garam Tbk needs to focus on better liquidity management and strategic initiatives. Management should be proactive in analyzing the factors affecting the financial performance of the company and take necessary actions to improve the situation. With careful management and the right strategies, PT Gudang Garam Tbk is expected to improve its financial performance and maintain stability in the long term